ECONOMIC ENVIRONMENT THE ACTIVITIES OF PHARMACEUTICAL ORGANIZATIONS - E. Manvelyan; R. Petinov; M. Manvelyan (Вестник Северо-Кавказского федерального университета, 2022)
Pharmaceutical business in modern conditions is for entrepreneurs and investors a very attractive and promising area of activity that requires further comprehensive research in the field of Economics and management. The rapid pace of development of the pharmaceutical industry, the emergence of pharmacy chains, conducting a coordinated marketing and pricing policy, demanded a revision of the long-standing hypothesis that the products of the pharmaceutical industry is in demand regardless ofthe realities ofeconomic and political life. The role of rational organization of relations between pharmacy organization and its business environment as one of the most importantfactors of modern Pharma-Economics is defined and the conclusions about the main directions of ensuring the effectiveness of the individual organization are drawn.